Book Review of "Race & Rurality: Considerations for Advancing Higher Education Equity" - Rachelle Kuehl (Journal of Research in Rural Education, 2024)
Edited by Tyler Hallmark, Sonia Ardoin, and Darris R. Means, Race and Rurality: Considerations for Advancing Higher Education Equity brings together higher education scholars from across the United States to discuss the specific needs of rural Students of Color and the many innovative ways institutions have sought to address them. The book is divided into four sections, the first of which sets the stage for readers' understanding of rurality and the unique challenges rural Students of Color face with regard to accessing higher education. The second section concerns attempts to ameliorate these access issues, in part by reframing the discussion from one focused on what rural Students of Color and their communities lack to one that highlights their cultural wealth (Crumb et al., 2021; Yosso, 2005). In the third section, authors explore the experiences rural Students of Color have while transitioning to college, and the fourth and final section picks up this discussion by describing mentoring and other structural supports that have led to successful outcomes for students from various racial, cultural, and geographic backgrounds. Interspersed among longer, research-focused pieces are shorter chapters (Chapters 4"5, 10"13, 18"19, and 24"25) the editors refer to as "Notes from the Field." With the exception of Chapter 5, these chapters highlight programs and practices that serve rural Students of Color as they prepare for, and later attend, college. (In Chapter 5, Koricich reports on data gleaned from a larger quantitative study that introduced a metric to designate institutions as rural-serving institutions [RSIs], finding a great degree of overlap among RSIs and institutions designated as minority-serving.